2009
DOI: 10.1002/mrc.2460
|View full text |Cite
|
Sign up to set email alerts
|

Proparacaine complexation with β‐cyclodextrin and p‐sulfonic acid calix[6]arene, as evaluated by varied 1H‐NMR approaches

Abstract: This study focused on the use of NMR techniques as a tool for the investigation of complex formation between proparacaine and cyclodextrins (CDs) or p-sulfonic acid calix[6]arene. The pH dependence of the complexation of proparacaine with beta-CD and p-sulfonic acid calix[6]arene was studied and binding constants were determined by (1)H NMR spectroscopy [diffusion-ordered spectroscopy (DOSY)] for the charged and uncharged forms of the local anesthetic in beta-CD and p-sulfonic acid calix[6]arene. The stoichiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 41 publications
(23 reference statements)
1
16
0
3
Order By: Relevance
“…The pH of the complexation media was shown to be an important factor for enhancing solubility of the local anesthetics, tetracaine and proparacaine, with 125 and β‐cyclodextrin. For both guest molecules, interaction at acidic pH is driven by ion pairing of the ammonium group of drug and sulfonate group of CA.…”
Section: Inclusion Complexes Of Aminocalix[n]arenesmentioning
confidence: 99%
“…The pH of the complexation media was shown to be an important factor for enhancing solubility of the local anesthetics, tetracaine and proparacaine, with 125 and β‐cyclodextrin. For both guest molecules, interaction at acidic pH is driven by ion pairing of the ammonium group of drug and sulfonate group of CA.…”
Section: Inclusion Complexes Of Aminocalix[n]arenesmentioning
confidence: 99%
“…In particular, there is an established evidence base confirming that water-soluble calix[n]arenes which possess sulfonate groups in the 4-position on the upper rim are capable of solubilising drug molecules which otherwise possess poor solubility in aqueous media [9][10][11][12][13][14][15][16][17][18][19][20][21]. However, few investigations into the properties and utility of simple calix[4]resorcinarenes which bear sulfonate groups in the 2-position on the upper rim have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Para-Sulfonatocalix [6]arene was shown to form complexes with the local anaesthetics tetracaine and proparacaine in their protonated forms, which would be present in vivo at physiological pH [55,56]. para-Sulfonatocalix [6]arene formed a strong, stoichiometric host-guest complex with each molecule which was confirmed by NMR and other spectroscopic studies.…”
Section: Sulfonatocalix[n]arenes For Drug Solubilizationmentioning
confidence: 64%
“…The association between para-sulfonatocalix [6]arene and the nonprotonated proparacaine was demonstrated to be considerably weaker. Indeed, studies revealed that the ionized amino groups are held closely to the calixarene cavity, highlighting the importance of ionic interactions in complex formation with calix[n]arenes in addition to any considerations of the hydrophobic effect [55,56]. [4]arene and para-sulfonatocalix [6]arene were employed in investigations into the solubilization of the hydrophobic anticonvulsant drug carbamazepine [57].…”
Section: Sulfonatocalix[n]arenes For Drug Solubilizationmentioning
confidence: 99%